Teacher’s ICT Competency: Principal Instructional E-Supervision and Learning Organization as Predictor for Technology Integration in the Classroom - Rasdiana, Rasdiana; Wiyono, Bambang Budi; Imron, Ali (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
This study was conducted to examine how the contributions of instructional e-supervision by the school principal and learning organisation affect the teachers’ technology, information, and communication (ICT) competencies based on the teacher professional digital competence (TPDC) framework in the process of integrating technology into teaching. The method used was quantitative analysis with multiple linear regression analysis using SPSS 25. The population in this study consisted of 428 teachers from public and private high schools in the city of Makassar. A sample of 257 was obtained using random sampling techniques. The research results in the first hypothesis showed an influence of instructional e-supervision by the school principal on the ICT competence of teachers. In line with this, the second hypothesis, learning organisation, also contributes to the teachers’ ICT competencies. Finally, the third hypothesis indicates a simultaneous influence of instructional e-supervision by the school principal and learning organisation on teachers’ technology, information, and communication (ICT) competencies with a coefficient of determination of 56.2%.